PERSEPSI REMAJA TERHADAP PERILAKU HOMOSEKSUAL: Adolescents' Perceptions of Homosexual Behavior - Nanang Khosim Azhari; Tuti Anggarawati; Nadhea Bunga Aprilia; Tria Friska Ningrum (JURNAL KEPERAWATAN SISTHANA, 2019)
Homosexuals or currently better known as LGBT (lesbian, gay, bisexual and transgender) is a phenomenon that has graced the media lately. Starting from the prosecution for legalizing same-sex marriage, the pros and cons of its existence, prostitution of minors for gays to prosecution by certain groups to criminalize homosexuals. Although homosexuals have existed for a long time, it is not yet known for certain the cause of this same-sex liking. Including the debate whether homosexuality is classified as a nuisance, risk or grace (normal). Homosexuality is a feeling of being attracted to the same sex (Stuart, 2013). Homosexuality does not occur between men and men (gay) or women and women. Another understanding according to Behrman, et al (2012) states that homosexuality is a physical and romantic force of the same sex. Currently, the phenomenon of homosexuality is better known as the term LGBT (lesbian, gay, bisexual and transgender). This phenomenon has existed since ancient times, but nowadays homosexual behavior has begun to tend to be carried out openly. This is different from ancient times where homosexual behavior was carried out in secret (Budiarty, 2011).